One method to determine the solution values at the boundary for the vertical two-dimensional equation system - Lich, Tran Gia (Vietnam Journal of Mechanics, 1998)
In this paper, the boundary conditions for modified Navier-Stokes equations system are presented, and the complementary equations on the boundaries are established.